TELAAH KEWENANGAN MAHKAMAH KONSTITUSI - Philips A. Kana (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
Based on the amendment of UUD 1945 the position of state organizations is placed based on the spirit of constitution reformation. It is the form of maintenance on differentiates principal / authority divisions, checks and balance systems to the constitutional process. The Constitutional Court that is one of the highest judgmental institutions has a series of duties and authority will colour the state structure systems of Indonesia.